"Liquid‐Liquid‐Solid"‐Type Superoleophobic Surfaces to Pattern Polymeric Semiconductors towards High‐Quality Organic Field‐Effect Transistors. (1st September 2013) - Wu, Yuchen; Su, Bin; Jiang, Lei; Heeger, Alan J.
<x xml:space="preserve">Abstract</x> Precisely aligned organic‐liquid‐soluble semiconductor microwire arrays have been fabricated by "liquid‐liquid‐solid" type superoleophobic surfaces directed fluid drying. Aligned organic 1D micro‐architectures can be built as high‐quality organic field‐effect transistors with high mobilities of >10 cm2·V−1·s−1 and current on/off ratio of more than 106. All these studies will boost the development of 1D microstructures of organic semiconductor materials for potential application in organic electronics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>